Mitochondrial susceptibility in a model of paraquat neurotoxicity - Czerniczyniec, Analia (2013)
Paraquat is a highly toxic herbicide capable of generating oxidative stress and producing brain damage after chronic exposure. The aim of this research was to investigate the contribution of mitochondria to the molecular mechanism of apoptosis in an in vivo experimental model of paraquat neurotoxicity. Sprague-Dawley adult female rats received paraquat (10 mg/kg i.p.) or saline once a week during a month. Paraquat treatment increased cortical and striatal superoxide anion levels by 45% and 18%, respectively. As a consequence, mitochondrial aconitase activity was significantly inhibited in cerebral cortex and striatum. Paraquat treatment increased cortical and striatal lipid peroxidation levels by 16% and 28%, respectively, as compared with control mitochondria Also, cortical and striatal cardiolipin levels were decreased by 13% and 49%, respectively. Increased Bax and Bak association to mitochondrial membranes was observed after paraquat treatment in cerebral cortex and striatum. Also, paraquat induced cytochrome c and AIF release from mitochondria. These findings support the conclusion that a weekly dose of paraquat during four weeks induces oxidative damage that activates mitochondrial pathways associated with molecular mechanisms of cell death. The release of apoptogenic proteins from mitochondria to cytosol after paraquat treatment would be the consequence of an alteration in mitochondrial membrane permeability due to the presence of high superoxide anion levels. Also, our results suggest that under chronic exposure, striatal mitochondria were more sensitive to paraquat oxidative damage than cortical mitochondria. Even in the presence of a high oxidative stress in striatum, equal levels of apoptosis were attained in both brain areas.